2009
DOI: 10.1021/la903236d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mold Rising Angle and Polymer Concentration in Solvent-Assisted Molding

Abstract: We investigated the capillary rise of a thin polymer solution in a simple soft lithographic technique termed "solvent-assisted molding (SAMo)" by using various mold rising angles and polymer concentrations in a good solvent. For patterning and mold materials, poly(methyl methacrylate) (PMMA, M(w) = 120,000) in toluene and poly(dimethyl siloxane) (PDMS) were mostly used. It was found that the capillary rise takes place in two steps: (i) a low-viscosity polymer solution rapidly rises into the cavity (<10 s) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…134 In this way, various micro- or nanopatterns of thermoplastic polymers such as PMMA, PS and PLGA have been constructed with high pattern fidelity. 33,84,85 It is noted in this regard that PMMA and PS have relatively high elastic modulus on the order of several GPa, capable of rendering several tens of nanometer patterns with high physical integrity.…”
Section: Synthetic Polymers and Their Properties/uses In Patterning Mmentioning
confidence: 99%
“…134 In this way, various micro- or nanopatterns of thermoplastic polymers such as PMMA, PS and PLGA have been constructed with high pattern fidelity. 33,84,85 It is noted in this regard that PMMA and PS have relatively high elastic modulus on the order of several GPa, capable of rendering several tens of nanometer patterns with high physical integrity.…”
Section: Synthetic Polymers and Their Properties/uses In Patterning Mmentioning
confidence: 99%
“…This technique generates features that are connected by a residual layer, unlike MIMIC. The patterns generated by SAMIM are affected by various parameters such as mold rising angle (angle between substrate and mold sidewall), concentration of the material being molded, and the amount of material being molded [50]. The capillary rise of the material on softening with the solvent can be controlled with the time of contact of the mold.…”
Section: Micromolding Allied Technique-samimmentioning
confidence: 99%
“…Some studies have reported the use of polymers to fabricate superhydrophobic surfaces. 2,[12][13][14][15][16][17][18][19][20][21][22][23] Before the polymer casting step, fabrication of the mold plays an important role, and many techniques such as mechanical machining, electrochemical machining, electrical discharge machining and laser beam machining are available for mold fabrication. Among them, laser beam machining offers many advantages such as freedom to use various process materials and simplicity of fabrication.…”
Section: Introductionmentioning
confidence: 99%